Deep Vein Thrombosis in Obstetric Patients: Diagnosis and Risk Factors - Boer, Karin de; Büller, Harry R; ten Cate, Jan W; Levi, Marcel (Thrombosis and Haemostasis, 1992)
This study was performed to assess the prevalence of deep vein thrombosis (DVT) in consecutive obstetric patients with clinical symptoms of DVT, using impedance plethysmography (IPG) as the diagnostic method and to establish the safety of withholding anticoagulant therapy in patients with a repeatedly normal IPG. In addition, in patients with DVT the prevalence of coagulation and fibrinolytic disorders, which may explain the occurrence of venous thrombosis was investigated.Of the 77 obstetric patients with symptoms of DVT 32 (42%) had an abnormal IPG. The remaining 45 patients had a repeatedly normal IPG and showed no venous thromboembolism during a 6 months follow-up period. Twenty percent (six patients) of the patients with an abnormal IPG had a coagulation or fibrinolytic abnormality. These observations suggest that serial IPG can be used effectively in the management of obstetric patients with clinically suspected DVT and that hemostatic abnormalities are frequently found in those patients with DVT